Analisis Isi Lirik Lagu “USIK” Karya Feby Putri: (Musik Sebagai Media Komunikasi Untuk Menuangkan Perasaan) - Arfian Suryasuciramdhan; Muhamad Syarif Hidayatullah; Anisa Nurbaiti; Ariani Galuh (Lembaga Pengembangan Kinerja Dosen, 2024)
Music has been a part of human life for a long time. It influences people's behavior and is an important component of culture. Music can convey messages through tonal sentences, expressing human emotions and feelings that are sometimes difficult to express directly. Song is a form of sound art that combines rhythmic sounds and musical instruments. They serve as a medium for people to express their thoughts and feelings. Song lyrics have a linguistic function, conveying the author's feelings and experiences. Emotions are subjective and related to psychology. They have an evaluative function, helping individuals understand their desires and the meaning of things. This research uses a literature review method to analyze the song